RETRACTED: Correlation analysis between clinical effective emotional treatment and plasma N-methyl-D-aspartate receptor function-related indexes - Feng, Zuxing; Li, Yanli; Cai, Ying; Yang, Fan; Zhou, Xiangfeng; Feng, Maoyang; Wu, Li (Frontiers in Neuroscience, 2025)
BackgroundWith the use of ketamine, Glutamate (Glu) system has gradually become the focus of antidepressant effects. N-methyl-D-aspartate receptor (NMDAR), as one of the major ionic glutamate receptors, plays a dominant role in antidepressant effects, especially in synaptic plasticity. Few studies have been conducted on changes of NMDAR-related indicators and inflammatory cytokines in major depressive disorder (MDD) patient’s peripheral blood before and after effective clinical perceptual recovery. This study aims to investigate changes in plasma biomarker levels related to NMDAR function in MDD patients receiving effective antidepressant treatment and their relationship with clinical outcomes.MethodsA total of 70 subjects of MDD having been discharged with an improvement rated a 50% or greater reduction by the Hamilton Depression Scale (HAMD-17) were hereby recruited. Changes in scores on the Symptom Checklist-90 (SCL-90), Self-rating Anxiety Scale (SAS), Self-rating Depression Scale (SDS), HAMD, and Hamilton Anxiety Scale (HAMA) were compared before and after therapy. Plasma D-serine (DSR), Glycine (Gly), Threonine (Thr), Glu, serine hydroxymethyltransferase (SHMT), interleukin (IL)-6, IL-8, IL-1β, IL-17, and tumor necrosis factor-alpha (TNF-α) were detected using Enzyme-linked immunosorbent assays. Subsequently, ratios of Thr/Gly and DSR/Gly were calculated, and differences between each biomarker before and after therapy were determined.Results(i) Plasma glutamate levels in MDD patients had increased at discharge and decreased levels of IL-17, IL-1β, IL-6, TNF-α, and IL-8. (ii) The change in total scores of HAMD and HAMA before and after hospitalization was weakly negatively correlated with the difference in IL-1β; the change in cognitive impairment was negatively correlated with the difference in Gly. (iii) The difference of IL-6 after effective antidepressant treatment was positively correlated with the difference in total HAMD score and the difference in despair. The difference in anxiety/somatization was positively correlated with that in IL-17, that in DSR and that in TNF-α, while being negatively correlated with that in IL-1β.ConclusionIndicators related to NMDAR function, including Glu, IL-6, IL-8, IL-1β, IL-17, and TNF-α, were changed after effective antidepressants treatment in patients with MDD at an acute stage. For patients with acute MDD, after effective antidepressant treatment, the greater the improvement in cognitive impairment, the smaller the change in Gly. The improvement of depressive and anxiety symptoms, the reduction of feelings of despair, and the alleviation of somatic anxiety symptoms are associated with inflammatory cytokines.